Occupational infections with bloodborne pathogens among medical personnel as a public health task - Gańczak, Maria (Przewodnik Lekarza/Guide for GPs, 2010)
Based on medical literature and author’s own research the paper provides arguments that occupational infections with blood-borne viruses among health care workers create a significant problem faced by Poland as well as many other countries. It appears to be a challenge for public health in the context of the urgent need of legislation acts contributing to the reduction in a prevalence of blood-borne infections in medical personnel. From Polish perspective mandatory training in infection control for all working in the health care sector, universal implementation of safe medical devices, increase in HBV vaccination coverage, adoption of universal, national exposure information network and periodical checking for anti-HCV seem to be the most important issues to resolve.